1992
DOI: 10.1149/1.2069348
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of a Primary Zinc/Air Battery

Abstract: The mathematical model developed by Sunu and Bennion has been extended to include the separator, precipitation of both solid ZnO and K2Zn(OH)4, and the air electrode, and has been used to investigate the behavior of a primary Zn-Alr battery with respect to battery design features. Predictions obtained from the model indicate that anode material utilization is predominantly limited by depletion of the concentration of hydroxide ions. The effect of electrode thickness on anode material utilization is insignifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 14 publications
0
43
1
Order By: Relevance
“…Clearly, the Zn(0001) surface is a bad model for bulk dissolution since the overpotential is poorly estimated to be 0.70 V, far from the experimentally measured one, i.e. 0.05-0.1 V. 41,42 The reason for this huge difference is that after dissolution of a single Zn atom the surface is left with a vacancy, hence the adsorption energy is higher. Similarly, black and blue lines in Fig.…”
Section: 43mentioning
confidence: 99%
“…Clearly, the Zn(0001) surface is a bad model for bulk dissolution since the overpotential is poorly estimated to be 0.70 V, far from the experimentally measured one, i.e. 0.05-0.1 V. 41,42 The reason for this huge difference is that after dissolution of a single Zn atom the surface is left with a vacancy, hence the adsorption energy is higher. Similarly, black and blue lines in Fig.…”
Section: 43mentioning
confidence: 99%
“…The durability of the Zn-air battery has been one-dimensionally modeled, considering the effects of ZnO precipitates [14][15][16][17]. The improved models were used to analyze the experimental discharge behavior of Zn-air batteries, involving the effects of a microporous separator and a porous air cathode [14].…”
Section: Introductionmentioning
confidence: 99%
“…The improved models were used to analyze the experimental discharge behavior of Zn-air batteries, involving the effects of a microporous separator and a porous air cathode [14]. Another model that was combined with a dilute solution approach [15] has achieved good agreement with galvanostatic experiments where the charging-discharging behavior of an electrically rechargeable Zn-air battery was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Their simulations showed the inhomogeneous precipitation of ZnO and investigated the shape change of the Zn electrode during cycling. In 1992, Mao and White [135] developed an extended model that also resolved the separator and air electrode. They found that K 2 Zn(OH) 4 does not precipitate and compared simulated cell voltages with experimental measurements.…”
Section: Cell Modelingmentioning
confidence: 99%